Statcom Performance Analysis In Improving Voltage Stability In Distribution Networks With High Renewable Energy Penetration - Siregar, Andi (Cattleya Darmaya Fortuna, 2025)
The increasing penetration of inverter-based renewable energy generators (PV/wind) in distribution networks raises new challenges related to voltage stability due to active power variability, phase imbalance, and local reactive capacity limitations. This paper analyzes the performance of Static Synchronous Compensator (STATCOM) in improving voltage stability in distribution networks with high renewable energy penetration through detailed modeling, design/comparison of control methods, and evaluation of their practical implications. The system model includes a VSC-based STATCOM representation in a dq framework with a phasor follower (PLL), DC-link dynamics, and Volt/VAR coordination with other voltage control devices (OLTC, capacitor bank, and DER inverter). Three control schemes are studied and compared—(i) set-point voltage regulation with PI anti-windup, (ii) adaptive Q–V droop characteristic based on load voltage sensitivity, and (iii) robust control with fault current feed-forward—focusing on the response to fast disturbances (irradiance/wind ramps, large motor startups, and single-phase-to-ground sags) and continuous operating conditions (daytime reverse power flow, load imbalance). Case studies are conducted on a representative medium-sized distribution feeder, with a multistage renewable penetration scenario (30–70% of peak load) and STATCOM locations selected based on voltage sensitivity index and reactive capacity constraints. Time-based simulation results show that STATCOM integration improves the voltage profile along the feeder, accelerates post-disturbance voltage recovery (shorter settling time and smaller overshoot), suppresses pu deviation at critical buses, reduces voltage equipment switching operations (more stable VVO coordination), and reduces network losses under several peak load and rapidly changing weather scenarios. In addition, STATCOM helps maintain the LVRT/HVRT limits of DER inverters so that the dynamic interactions of the system remain under control during sag/swell events. The contributions of this paper are (1) an integrated framework for modeling and evaluating STATCOM performance in high DER environments, (2) a systematic comparison of several control strategies with uniform performance indicators (voltage profile, recovery time, voltage stability index, and losses), and (3) practical recommendations for placement and set-point adjustments to be compatible with utility operating practices and grid codes. These findings provide a technical foundation for distribution planners and operators in formulating STATCOM-based flexible reinforcement strategies to support large-scale renewable integration without compromising voltage quality.